MDAB programme is a waste of money? / Nor Hazizah Julaihi … [et al.] - Julaihi, Nor Hazizah; Mohamadin, Mohammad Isa; Mohamed, Bebe Norlita; Karim, Mariathy (Penerbit UiTM (UiTM Press), 2017)
The MDAB programme is a remedial course introduced by Universiti Teknologi MARA (UiTM) in June 2010. The main objective of the programme is to give an opportunity to Bumiputera students having under qualified entry results and coming from low income families to further their tertiary studies in UiTM. The students entering this programme are fully sponsored and to date about 22000 students have undergone this programme and about RM20 million has been spent just for the students’ allowance. Thus, this research was embarked to investigate the overall performance of the students in this programme in order to justify that the money invested was indeed well spent and also such remedial courses have helped the students. The performance of all MDAB students for the last nine semesters as well as the performance of a particular MDAB programme namely Pre-Science at UiTM Sarawak are reported in this paper. The results showed that 83.43% of the overall MDAB students managed to complete the courses and continued their studies at diploma level. However, only 70.94% of Pre-Science students in UiTM Sarawak managed to complete their courses. In general, the overall performance showed that the programme has indeed succeeded in helping the students to further their studies at a higher level.